1986
DOI: 10.1177/002188638602200409
|View full text |Cite
|
Sign up to set email alerts
|

Common Behavior Changes in Successful Organization Development Efforts

Abstract: Finding that the field of organization development (OD) suffers from a lack of a unifying theory ofplanned organizational change and the difficulty of integrating research based on diverse methods and models, the authors propose a model in which on-the-job behaviors of organization members act as important mediating variables of organizational change. The article discusses a study seeking to identify and specify common behavior changes characteristic of successful change efforts. The authors surveyed 42 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
7

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 17 publications
2
56
0
7
Order By: Relevance
“…In addition it has been recognized that the behavioural responses can be grouped into repeating patterns. Researchers such as Ashforth and Lee [7], Jaworski and Young [8], Merchant [9], Porras and Hoffer [10] and Vardi and Wiener [11] have all grouped behaviour patterns into repeating sets. They have particularly focused on those that are considered to be negative patterns in terms of organizational performance so that they can be identified and removed.…”
Section: Individual Behaviour Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it has been recognized that the behavioural responses can be grouped into repeating patterns. Researchers such as Ashforth and Lee [7], Jaworski and Young [8], Merchant [9], Porras and Hoffer [10] and Vardi and Wiener [11] have all grouped behaviour patterns into repeating sets. They have particularly focused on those that are considered to be negative patterns in terms of organizational performance so that they can be identified and removed.…”
Section: Individual Behaviour Patternsmentioning
confidence: 99%
“…improved performance [10]. Research into specific OJB patterns is relatively infrequent but has been extensively discussed by Robertson et al [17].…”
Section: Organizational Behaviour Patternsmentioning
confidence: 99%
“…Christian, 1984) or otherwise (West & Farr, 1989). This is partly as a number of different groups have investments in the academic curriculum, and therefore must be involved in the decision-making process if development is to take place (Porras & Hoffer, 1986). Also, the decisions that need to be made are complex, as they require consideration of the strengths of the current academic curriculum, as well as an examination of areas that could be further improved.…”
Section: Participation In Changementioning
confidence: 99%
“…Studies by Porras and Hoffer (1986) have shown that certain behaviors are critical in organization change programs. They found that openly communicating (sharing intentions, listening) and collaborating (making decisions in teams) were the behaviors most related to success.…”
Section: Involving All Levels Of Management In Communicationmentioning
confidence: 99%